(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article presents a definition of linguistic terms of "realiа", denotes the functionality of this unique category of words as a necessary component of national identity for the transmission of text in different languages. In the article, just the different ways, the issues related to national realities as elements of the language picture of the world and to their translation. The particular interest to study the different ways, to translate the words-realia from the point of view of their role in a literary text. Study of realia is so great that the study did not complete it would fit in the scope of this article. Realia characteristic sublanguage literature and the media, is inextricably linked to the culture of a particular people, are commonly used for the language of the people and foreign to other languages. The features of the realities of translation, it should be noted that scholars have noted the great importance of the linguistic unit. Conclusions are based on the results of the conducted linguistic experiment.